Case Report: Camrelizumab plus gemcitabine followed by concurrent chemoradiation for HPV-positive and PD-L1-positive tonsillar squamous cell carcinoma - Xuesong Li; Bianhong Wang; Hao Liu; Zhuo Yu (Frontiers in Immunology)
Modality treatment including surgery, chemotherapy, radiation and immunotherapy was considered as standard strategy for tonsillar squamous cell carcinoma (TSCC). We reported a case of a 78-year-old man under severe underlying medical conditions who diagnosed with human papillomavirus (HPV)-positive and programmed death ligand 1 (PD-L1)-positive TSCC. He was administered camrelizumab combined with gemcitabine (GEM) for 8 cycles with partial response. Then, we gave him concurrent nanoparticle albumin-bound paclitaxel (nab-paclitaxel)-based chemoradiation. Eventually, this patient achieved complete response without severe adverse events. After a 12-month follow-up, he had no recurrence or metastasis.